2020
DOI: 10.1016/j.critrevonc.2020.103075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postoperative complications on survival and recurrence after surgery for breast cancer: A systematic review and meta-analysis

Abstract: Background: This systematic review investigated the impact of complications on long term outcomes for patients with primary invasive operable breast cancer.Methods: A systematic review was performed using appropriate keywords, and meta-analysis using a random effects model completed.Results: Ten retrospective cohort studies, including 37657 patients were included. Five studies identified a relationship between wound complications, infection and pyrexia and recurrence or recurrence-free survival. Risk of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…On average, the resection volumes in this study remained under this threshold. Rate of surgical site infections and wound complications after breast cancer surgery vary from less than 5% to more than 30% depending on timing and definition [21], [61], [62]. In our series, the rate of infection or wound complications (5%), was similar to other studies [63], [64].…”
Section: Discussionsupporting
confidence: 86%
“…On average, the resection volumes in this study remained under this threshold. Rate of surgical site infections and wound complications after breast cancer surgery vary from less than 5% to more than 30% depending on timing and definition [21], [61], [62]. In our series, the rate of infection or wound complications (5%), was similar to other studies [63], [64].…”
Section: Discussionsupporting
confidence: 86%
“…We believe that the main reasons could be as follows. First, the interventions (i.e., changing of dressings and vital sign assessment) for patients with conventional care are mainly performed by students or nurses alone, while the managing physicians are mainly responsible for major systemic treatment, and there might be a lack of timely and direct communication between them resulting in lack of adequate attention to factors that might have potentially led to these complications [23]. The collaborative care-based nursing can effectively avoid the abovementioned shortcomings as it integrates the medical and nursing personnel to form an intervention team, which improves the standardization and systematization of treatment and results in better treatment outcomes for the patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the increase of SIR, such as NLR, is a risk factor for worse long‐term prognosis 21,34 . The effect of postoperative complications on tumor survival is still controversial, but many studies have shown that postoperative complications are independent risk factors for OS 35–38 . As the decision curve shows, although the univariate model can predict the prognosis of patients to a certain extent and range, nomogram shows better prediction accuracy and applicability in a more extensive area.…”
Section: Discussionmentioning
confidence: 99%